Economic Renewal and Demographic Change : an Evaluation of Policies for Functioning Local Labour Markets in the Nordic Countries - Edvardsson, Ingi Runar; Heikkilä, Elli; Johansson, Mats; Persson, Lars Olof; Schmidt, Torben Dall; Stambøl, Lasse Sigbjørn (Siirtolaisuusinstituutti, 2007)
Although unemployment is a persistent problem in several countries, the issue of labour shortages is now emerging as an increasingly stubborn obstacle to growth across Europe. The concurrence of relatively high levels of unemployment and labour shortages essentially reflects the highly differentiated nature of the labour market and the lack of coherence between the growth of demand for labour and the skills on offer among those looking for work. Recruitment difficulties tend to be reported in particular sectors even in periods of recession. In periods of recovery and as unemployment falls – or, more accurately, as the excess supply of labour diminishes – it is to be expected that skill bottlenecks will become more serious, the more so, naturally, in regions where unemployment is relatively low, but also in other areas where the skills of the unemployed do not match the demands of employers. If economic growth at present rates is sustained over the longer term, the problem of this “skills imbalance” is expected to be compounded by the projected slowdown in labour force growth over the next 10-15 years. In some regions we have already seen a decline. EU countries differ considerably in terms of their internal labour market structures and economic performance. Well functioning labour markets are those which secure high labour force participation for all groups on the labour market, where transition from unemployment, sickness or education to work is relatively easy, and opportunities to lifelong learning are present. Labour market performance has been closely related to labour market and welfare policies. In this paper have chosen to analyse national policies on welfare and labour markets. Introduction Emerging Challenges to Labour Market Efficiency Purpose of the Paper Northern Landscapes of Demographic Change A Typology with Regard to Natural Population Change and Migration Country Differences Explanatory Components Modes of Renewal of Local Economies and Labour Markets A Career Approach Nordic Employment ...